Effectiveness of the Interactive E-Learning Community (Ielc) On the Practice of Self-Regulated Learning for Secondary Schools in Kuala Lumpur. - Vighnarajah, (2008)
In an examination-dominated culture in the Malaysian schools, the current education system has been criticized for lacking in fostering self-regulated learning strategies. Effective practice of self-regulated learning has been perceived as key for learner to succeed academically and after the schooling years. Poor practice of self-regulated learning can result students in being able only to memorize information and reproduce it during examination. Thus, the development of the iELC discussion platform was proposed to complement the traditional teacher-centered instruction and to inculcate the practice of self-regulated learning. The iELC discussion platform is an online discussion platform, developed using the open source Moodle software to encourage students’ participation in an online learning community on the sharing of knowledge and the learning of the Form Four KBSM Physics subject. The objectives of the study were; (i) to develop an online discussion platform termed as the iELC discussion platform; and (ii) to investigate the effectiveness of the iELC discussion platform in advancing the practice of self-regulated learning strategies in the learning process. The pretest-posttest and posttest only non-equivalent research design was employed in this study. The schools were selected in a two-stage cluster sampling technique. In the first stage, two zones in Kuala Lumpur were randomly selected to represent the selection of the experimental and control group. In the second stage, two schools were randomly selected from each of these zones to represent the experimental and control schools, giving a total of four schools. Samples (n = 102) consisted of Form Four Physics students from four regular national secondary schools in Kuala Lumpur. For a duration of eight weeks, fifty students from two regular national secondary schools used the iELC discussion platform and also face-to-face discussion to study the topic of “Kinematics and Motion” in the Form Four KBSM Physics. The other two classes with fifty-two students acted as the control groups and only followed the face-to-face discussion. The Motivated Strategies for Learning Questionnaire (MSLQ) was used to measure the samples’ use of self-regulated learning strategies. The instrument consists of several subscales which are intrinsic goal orientation, extrinsic goal orientation, control of learning beliefs, self-efficacy for learning and performance, rehearsal, elaboration, organization, critical thinking, metacognitive self-regulation, time and study environment, effort regulation, peer learning and help seeking. Two-way analysis of variance was used to analyze the impact of the two independent factors (iELC discussion platform treatment and administration of pretest) on the dependent variable (self-regulated learning posttest mean scores). The main findings of the study indicated that participation in the iELC discussion platform was significantly effective in encouraging practice of self-regulated learning strategies in the learning process. Participation in the iELC discussion platform was particularly effective in encouraging practice of self-efficacy for learning and performance, rehearsal, elaboration, organization, time and study environment, effort regulation and help seeking. In conclusion, these findings suggest that students’ participation in the iELC discussion platform improved their use of self-regulated learning strategies.